Performance of extended space-time coding techniques for MIMO MC-CDMA systems - Bastos, J. (2012)
In this paper we consider a transmission system based on MC-CDMA, where signal spreading is performed entirely in the frequency domain. An extended spacetime coding technique, the Double Alamouti, is evaluated considering a MIMO channel. This assessment is made against standard Alamouti coding, for two different Tx/Rx antenna schemes (2x1 and 2x2). Numerical results, attained through system model simulations, are presented for performance evaluation under realistic scenarios considering some typical system impairments. These results show that in practical systems significant improvements can be achieved by using the Double Alamouti coding scheme.